2006
DOI: 10.1196/annals.1364.048
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder With Amnesia Following Asphyxiation

Abstract: We describe five cases of traumatic asphyxiation injury, each meeting diagnostic criteria for posttraumatic stress disorder (PTSD) and characterized by a range of postinjury cognitive impairment. Four patients exhibited dense retrograde amnesia, including absence of conscious memory for the traumatic event. Appreciation of these asphyxiation cases, which involve temporally extended trauma exposure, may help resolve arguments regarding the possibility of co-occurrence of PTSD and neurological amnesia based excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…In both of these cases a specific memory for the trauma context is not necessary for sensitization of subsequent fear learning. This augmented fear conditioning is consistent with reports from PTSD patients exhibiting a greater propensity to develop new phobias and a greater reactivity to emotionally salient stimuli even under conditions in which patients may fail to remember the precipitating trauma (4). …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In both of these cases a specific memory for the trauma context is not necessary for sensitization of subsequent fear learning. This augmented fear conditioning is consistent with reports from PTSD patients exhibiting a greater propensity to develop new phobias and a greater reactivity to emotionally salient stimuli even under conditions in which patients may fail to remember the precipitating trauma (4). …”
Section: Discussionsupporting
confidence: 88%
“…In the adult human and rodent, memories established within an emotionally charged environment are generally robust and not readily forgotten (1,2) and thus may provide important insights into the link between trauma related memory and PTSD. This link has been primarily explored in patients with mild traumatic brain injury and/or traumatic asphyxiation injury with post-traumatic amnesia (3,4,5) as well as in subjects with early life trauma occurring during the period of infantile amnesia (6). Despite this, the link between trauma-related memory and PTSD remains a point of controversy (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the neurocircuitry of fear learning was altered even though the learning originating in the infantile amnesia period was forgotten. Poulos et al (147) consider this augmented fear conditioning to be analogous to those types of PTSD patients who do not remember their precipitating traumatic event (e.g., asphyxiation with amnesia) yet exhibit a greater propensity for developing phobias and expressing reactivity to other emotional stimuli (148, 149). …”
Section: The Stress Acceleration Hypothesis Of Nightmaresmentioning
confidence: 99%
“…Layton, Krikorian, Dori, Martin, and Wardi (2006) demonstrated that people with amnesia following a trauma may still exhibit avoidance and hyperarousal to traumarelated stimuli in the absence of conscious recollection of the event. First, an overactive amygdala in response to trauma reminders and trauma-unrelated aversive stimuli has been observed in many studies .…”
Section: Structural and Functional Changes In Ptsdmentioning
confidence: 99%